Hubungan Tingkat Pengetahuan dengan Perilaku Membaca Label Gizi pada Remaja di SMKN 6 Kota Jambi - Hafifah, Hafifah; Indrawati, Iin; Hatussaadah, Siti Fati (Universitas Baiturrahim, 2025)
Label reading habits among adolescent consumers are still very lacking. Adolescents lack understanding regarding nutritional information which is an important part of nutrition labels. The purpose of this study was to determine the relationship between knowledge and behavior of reading nutrition labels among adolescents at SMKN 6 Jambi City. This study was a quantitative study with a cross-sectional design. Data collection was carried out by filling out a questionnaire about knowledge and behavior related to reading nutrition labels. The population in this study was 232 adolescents and a sample of 77 adolescents using a proportional random sampling technique. Data analysis in this study used the chi-square test. The level of knowledge in the poor category was 64.9%, while the behavior of reading nutrition labels in the poor category was 50.6%. The results of the statistical test using chi square showed a p-value of 0.562 (>0.05) which means there is no relationship between the level of knowledge and behavior of reading nutrition labels in adolescents. The conclusion of this study provides an overview of the importance of motivation and education for adolescents at SMKN 6 Jambi City regarding awareness of the importance of reading nutrition information.